ANALISIS PENGARUH STOCK SPLIT TERHADAP ABNORMAL RETURN DAN VOLUME PERDAGANGAN SAHAM PADA PERUSAHAAN BERTUMBUH DAN TIDAK BERTUMBUH (Studi Kasus Pada Bursa Efek Indonesia 2008-2012) - Oktaviana Sakti, Paramita; Rini DP, Irene (Faculty of Economics and Business Diponegoro University, 2013)
When the price of stock is too high, some investor is hard to reach the price so the go-public companies can do stock split. Stock split is one kind of corporate action implemented by companies in order torearrange stock price to be a more liquid range and provide more positive signal to investor. The aim of this study is to analyze the differences of abnormal return and trading volume activity on growth and non-growth firms before and after stock split.The study was conducted on 36 companies that are listed on the Indonesian Stock Exchange and they do stock split in the year 2008-2012. There are 31 companies listed as growth firms and 5 companies listed as non-growth firms. The category of growth and non-growth firms based on IOS (Investment Opportunity Set) proxy MVEBVE (Market to Book Value of Equity). This study used statistical analysis test two different test average with a 11-day observation period is t = -5 (5 days before stock split) , t=0 (event date) and t = 5 (5 days after stock split). The method of determination of sample using purposive sampling. Analyze data using Wilcoxon Signed Ranks Test.The result showed that there are significant differences between AAR of non-growth company & average TVA of growth company before & after stock split and also average TVA between growth and non-growth company after stock split. Meanwhile there are noÂ significant differences between AAR of growth company & average TVA of non-growth company before & after stock split and also AARÂ between growth and non-growth company after stock split